1999
DOI: 10.1007/s004670050572
|View full text |Cite
|
Sign up to set email alerts
|

Water transport in the immature rabbit collecting duct

Abstract: Immature animals have limited ability to concentrate the urine. This is in part the result of end-organ resistance to arginine vasopressin (AVP). To characterize this response, we measured water absorption in microperfused cortical collecting ducts (iCCD) and outer medullary CD (iOMCD) derived from 2- to 12-day-old rabbits. The roles of adenosine 3',5'-cyclic monophosphate (cAMP) and prostaglandins were investigated. Baseline osmotic water permeability (L(p), 10(-7) cm/atm per s) in the iCCD (20.3+/-2.4) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…2, the adult tubules had a larger increase in water permeability in response to ADH than did the neonatal tubules (260.1 ± 29.5 vs. 119.0 ± 12.5 µm/s; P < 0.05, n = 6). These results are comparable to previously reported findings (5,19,36).…”
Section: Camp Generationsupporting
confidence: 92%
“…2, the adult tubules had a larger increase in water permeability in response to ADH than did the neonatal tubules (260.1 ± 29.5 vs. 119.0 ± 12.5 µm/s; P < 0.05, n = 6). These results are comparable to previously reported findings (5,19,36).…”
Section: Camp Generationsupporting
confidence: 92%
“…Neonatal CT water permeability did not increase in response to vasopressin to the same extent as that seen in the adult [312][313][314][315]. Studies have shown that the phosphodiesterase activity is greater in the neonatal collecting tubule [313].…”
Section: Development Of Urinary Concentration and Dilutionmentioning
confidence: 57%
“…The response of the collecting tubule to vasopressin has been examined in vitro [312][313][314][315]. Neonatal CT water permeability did not increase in response to vasopressin to the same extent as that seen in the adult [312][313][314][315].…”
Section: Development Of Urinary Concentration and Dilutionmentioning
confidence: 83%
“…In the later process of dif-ferentiation, it develops a functional barrier, so that different fluid compositions are found at the luminal and basal sides [26,27]. It is unclear how far a change in the electrolyte environment is able to influence the development of the epithelium.…”
Section: Discussionmentioning
confidence: 99%